Bio-sensing of cadmium(II) ions using Staphylococcus aureus - Sochor, Jiri; Zitka, Ondrej; Hynek, David; Jilkova, Eva; Krejcova, Ludmila; Trnkova, Libuse; Adam, Vojtech; Hubalek, Jaromir; Kynicky, Jindrich; Vrba, Radimir; Kizek, Rene (Sensors (Basel, Switzerland), 2011)
Cadmium, as a hazardous pollutant commonly present in the living environment, represents an important risk to human health due to its undesirable effects (oxidative stress, changes in activities of many enzymes, interactions with biomolecules including DNA and RNA) and consequent potential risk, making its detection very important. New and unique technological and biotechnological approaches for solving this problems are intensely sought. In this study, we used the commonly occurring potential pathogenic microorganism Staphylococcus aureus for the determination of markers which could be used for sensing of cadmium(II) ions. We were focused on monitoring the effects of different cadmium(II) ion concentrations (0, 1.25, 2.5, 5, 10, 15, 25 and 50 μg mL(-1)) on the growth and energetic metabolism of Staphylococcus aureus. Highly significant changes have been detected in the metabolism of thiol compounds-specifically the protein metallothionein (0.79-26.82 mmol/mg of protein), the enzyme glutathione S-transferase (190-5,827 μmol/min/mg of protein), and sulfhydryl groups (9.6-274.3 μmol cysteine/mg of protein). The ratio of reduced and oxidized glutathione indicated marked oxidative stress. In addition, dramatic changes in urease activity, which is connected with resistance of bacteria, were determined. Further, the effects of cadmium(II) ions on the metabolic pathways of arginine, β-glucosidase, phosphatase, N-acetyl β-d-glucosamine, sucrose, trehalose, mannitol, maltose, lactose, fructose and total proteins were demonstrated. A metabolomic profile of Staphylococcus aureus under cadmium(II) ion treatment conditions was completed seeking data about the possibility of cadmium(II) ion accumulation in cells. The results demonstrate potential in the application of microorganisms as modern biosensor systems based on biological components.
Keywords: metabolismus; spectrophotometry; disacharidy; glutathiontransferasa; proteiny; sulfhydrylové sloučeniny; Disaccharides; Metallothionein; Glutathione Transferase; Staphylococcus aureus; Cell Proliferation; metalothionein; látky znečišťující životní prostředí; glutathiondisulfid; biosenzitivní techniky; Hydrolases; fosfatasy; hydrolasy; Phosphoric Monoester Hydrolases; Electrochemical Techniques; ureasa; elektrochemické techniky; electrochemistry; glutathion; Biosensing Techniques; Urease; high performance liquid chromatography with electrochemical detection; Sulfhydryl Compounds; metabolic activity; metabolome; biosensor; monosacharidy; microbiome; voltammetry; proliferace buněk; Environmental Pollutants; Glutathione; Metabolism; Brdicka reaction; cadmium; Glutathione Disulfide; kadmium; Proteins; Monosaccharides; Cadmium